1999
DOI: 10.1164/ajrccm.159.1.9803094
|View full text |Cite
|
Sign up to set email alerts
|

Intrapleural Urokinase versus Normal Saline in the Treatment of Complicated Parapneumonic Effusions and Empyema

Abstract: Intrapleural administration of fibrinolytic agents has been shown to be effective and safe in the treatment of loculated parapneumonic pleural effusions. However, controlled studies of the possible role of the activity of urokinase (UK) through the volume effect are lacking. We therefore investigated the hypothesis that UK is effective through the lysis of pleural adhesions and not through the volume effect. Thirty-one consecutive patients with multiloculated pleural effusions were randomly assigned to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
178
3
8

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(196 citation statements)
references
References 30 publications
7
178
3
8
Order By: Relevance
“…Thus, intrapleural fibrinolytic therapy to lyse pleural loculations has attracted ongoing interest since 1949(6) with small studies (7,8) demonstrating reductions in surgical intervention rates. Subsequently, the MIST (Multi-Centre Intrapleural Sepsis Trial)-1, the largest randomised controlled trial of intrapleural fibrinolytics (streptokinase) failed to demonstrate any benefits over placebo for pleural infection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, intrapleural fibrinolytic therapy to lyse pleural loculations has attracted ongoing interest since 1949(6) with small studies (7,8) demonstrating reductions in surgical intervention rates. Subsequently, the MIST (Multi-Centre Intrapleural Sepsis Trial)-1, the largest randomised controlled trial of intrapleural fibrinolytics (streptokinase) failed to demonstrate any benefits over placebo for pleural infection.…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinical relevance of pleural fluid drainage (rate and volume) as an outcome measure is unclear, the majority of published studies have used this variable as a primary outcome. 5,6 In addition, no local or systemic bleeding events were associated with the use of tPA in this patient population. Last, early instillation of tPA (within 24 hours) was associated with a shorter duration of chest tube placement, particularly when compared with late administration of tPA.…”
Section: Discussionmentioning
confidence: 75%
“…4 Two small sample randomized controlled trials in adults have shown that pleural fluid drainage is increased with fibrinolytics and that significant activation of systemic fibrinolysis does not occur. [5][6][7] Both streptokinase and urokinase have been used as intrapleural fibrinolytics in children. A recent placebo-controlled trial of intrapleural urokinase in children with complicated parapneumonic effusions demonstrated a reduced length of hospital stay in children who were treated with urokinase compared with the placebo group.…”
mentioning
confidence: 99%
“…These studies are split between one large trial (N = 454) that concludes that thrombolytics should not be used in the treatment of pleural effusion 1 and several smaller studies (N ≤ 100) in favor of the use of thrombolytics in the treatment of pleural effusion [2][3][4][5][6][7][8][9][10] . There are also three meta-analyses of the randomized, placebo-controlled trials written on this topic, all of which conclude that intrapleural thrombolytics likely reduce the need for surgical intervention in some patients, but that the data are heterogenous [11][12][13] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the nine studies that support the use of thrombolytic therapy, five had no control arm; two were retrospective reviews of cases of intrapleural alteplase treatment [2][3] ; two were single-arm prospective studies of similar cases [4][5] ; one was a randomized trial comparing the efficacies of intrapleural streptokinase and intrapleural urokinase, without a control group 6 ; two were single-center, randomized, placebo-controlled trials, using inclusion criteria that were too broad for this situation (patients were grouped together if they had either empyema or a complicated parapneumonic effusion, and only a subset of these patients had loculations) [7][8] ; and the remaining two papers were both double-blind, randomized studies that included patients who had been diagnosed with multiloculated pleural effusions based on ultrasound and/or CT evidence [9][10] . Both of these last studies also required participants to have failed simple tube drainage, which may indicate a blockage of free flow.…”
Section: Literature Reviewmentioning
confidence: 99%